Is the urban heat island exacerbated during heatwaves in southern Australian cities? - Cassandra D. W. Rogers; Ailie J. E. Gallant; Nigel J. Tapper (Theoretical and Applied Climatology, 2019)

Short-term changes in thermal perception associated with heatwave conditions in Melbourne, Australia - Cho Kwong Charlie Lam; Ailie J.E. Gallant; Nigel J. Tapper (Theoretical and Applied Climatology, 2019)

The microscale cooling effects of water sensitive urban design and irrigation in a suburban environment - Ashley M. Broadbent; Andrew M. Coutts; Nigel J. Tapper; Matthias Demuzere; Jason Beringer (Theoretical and Applied Climatology, 2018)

Seasonal, interannual and decadal drivers of tree and grass productivity in an Australian tropical savanna - Caitlin E. Moore; Jason Beringer; Randall J. Donohue; Bradley Evans; Jean‐François Exbrayat; Lindsay B. Hutley; Nigel J. Tapper (Global Change Biology, 2018)
Tree–grass savannas are a widespread biome and are highly valued for their ecosystem services. There is a need to understand the long‐term dynamics and meteorological drivers of both tree and grass productivity separately in order to successfully manage savannas in the future. This study investigated the interannual variability ( IAV ) of tree and grass gross primary productivity ( GPP ) by combining a long‐term (15 year) eddy covariance flux record and model estimates of tree and grass GPP inferred from satellite remote sensing. On a seasonal basis, the primary drivers of tree and grass GPP were solar radiation in the wet season and soil moisture in the dry season. On an interannual basis, soil water availability had a positive effect on tree GPP and a negative effect on grass GPP . No linear trend in the tree–grass GPP ratio was observed over the 15‐year study period. However, the tree–grass GPP ratio was correlated with the modes of climate variability, namely the Southern Oscillation Index. This study has provided insight into the long‐term contributions of trees and grasses to savanna productivity, along with their respective meteorological determinants of IAV .

Erratum to: Temperature and human thermal comfort effects of street trees across three contrasting street canyon environments - Andrew M. Coutts; Emma C. White; Nigel J. Tapper; Jason Beringer; Stephen J. Livesley (Theoretical and Applied Climatology, 2016)

Temperature and human thermal comfort effects of street trees across three contrasting street canyon environments - Andrew M. Coutts; Emma C. White; Nigel J. Tapper; Jason Beringer; Stephen J. Livesley (Theoretical and Applied Climatology, 2016)

The relationship between housing and heat wave resilience in older people - Margaret Loughnan; Matthew Carroll; Nigel J. Tapper (International Journal of Biometeorology, 2015)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Observed relationships between El Niño‐Southern Oscillation, rainfall variability and vegetation and fire history on Halmahera, Maluku, Indonesia - SANDER VAN DER KAARS; NIGEL TAPPER; ELLYN J. COOK (Global Change Biology, 2010)
A temporally high‐resolution palynological study of the uppermost section of core MD98‐2180 from Kau Bay, Halmahera, Indonesia, provides a vegetation and fire record covering the last 250 years. The record is compared with the Maluku Rainfall Index, Southern Oscillation Index (SOI) and southern hemisphere winter sea surface temperatures (SST) for the central Pacific Ocean based on instrumental data, as well as reconstructions of the SOI and the central Pacific SST and historically recorded El Niño events. The results show that significant El Niño events are generally associated with increased representation of Dipterocarpaceae pollen, probably reflecting the mass‐flowering of this taxon during El Niño‐Southern Oscillation (ENSO) droughts, and elevated charcoal levels, reflecting a greater incidence of fires during these extremely dry periods, while humid phases show increased fern numbers. Our findings demonstrate that pollen records ‘ecological’ in scale can provide useful additional proxy records of ENSO events.

Aerosols and their influence on radiation partitioning and savanna productivity in northern Australia - Kasturi Devi Kanniah; Jason Beringer; Nigel J. Tapper; Chuck N. Long (Theoretical and Applied Climatology, 2010)

Climate extremes: progress and future directions - Lisa V. Alexander; Nigel Tapper; Xuebin Zhang; Hayley J. Fowler; Claudia Tebaldi; Amanda Lynch (International Journal of Climatology, 2009)

Investigating the climatic impact of urban planning strategies through the use of regional climate modelling: a case study for Melbourne, Australia - Andrew M. Coutts; Jason Beringer; Nigel J. Tapper (International Journal of Climatology, 2008)
Urban planning is a useful method for improving local climate and human health in cities through purposefully modifying urban land surface characteristics. This can reduce the potential risks of elevated city temperatures due to the urban heat island (UHI). Unfortunately, simple tools are not readily available for urban planners to assess the climatological impacts of various urban development scenarios. Urban modelling could be developed into such a tool to achieve this. This study attempts to design and evaluate a suitable tool for application in Melbourne, Australia. The Air Pollution Model (TAPM) was chosen to assess the impact of a long‐term urban planning strategy on local climate and the above canopy UHI in Melbourne. Improvements were made to TAPM by increasing the number of urban land‐use classes in the model and creating a higher resolution land cover database focused on housing density. This modified version of TAPM showed a good performance in replicating the surface energy balance compared with an observational flux tower site in suburban Melbourne during summer. TAPM simulated a mean maximum UHI intensity of 3–4 °C at 2 a.m. in January. A future UHI scenario was then examined (year 2030) using an urban land cover database derived from plans in the Melbourne 2030 urban planning strategy. Results highlighted specific areas where planning intervention would be particularly useful to improve local climates, namely activity centres and growth areas. The appropriateness of the use of TAPM and climate models as a tool in urban planning is also discussed. Copyright © 2008 Royal Meteorological Society

Local boundary-layer development over burnt and unburnt tropical savanna: an observational study - Chris K. Wendt; Jason Beringer; Nigel J. Tapper; Lindsay B. Hutley (Boundary-Layer Meteorology, 2007)

Savanna fires and their impact on net ecosystem productivity in North Australia - JASON BERINGER; LINDSAY B. HUTLEY; NIGEL J. TAPPER; LUCAS A. CERNUSAK (Global Change Biology, 2007)
Savannas comprise a large area of the global land surface and are subject to frequent disturbance through fire. The role of fire as one of the primary natural carbon cycling mechanisms is a key issue in considering global change feedbacks. The savannas of Northern Australia burn regularly and we aimed to determine their annual net ecosystem productivity (NEP) and the impact of fire on productivity. We established a long‐term eddy covariance flux tower at Howard Springs, Australia and present here 5 years of data from 2001 to 2005. Fire has direct impacts through emissions but also has indirect effects through the loss of productivity due to reduced functional leaf area index and the carbon costs of rebuilding the canopy. The impact of fire on the canopy latent energy exchange was evident for 40 days while the canopy was rebuilt; however, the carbon balance took approximately 70 days to recover. The annual fire free NEP at Howard Springs was estimated at −4.3 t C ha −1 yr −1 with a range of −3.5 to −5.1 t C ha −1 yr −1 across years. We calculated the average annual indirect fire effect as +0.7 t C ha −1 yr −1 using a neural network model approach and estimated average emissions of fine and coarse fuels as +1.6 t C ha −1 yr ‐1 . This allowed us to calculate a net biome production of −2.0 t C ha −1 yr ‐1 . We then partitioned this remaining sink and suggest that most of this can be accounted for by woody increment (1.2 t C ha −1 yr ‐1 ) and shrub encroachment (0.5 t C ha −1 yr ‐1 ). Given the consistent sink at this site, even under an almost annual fire regime, there may be management options to increase carbon sequestration by reducing fire frequency.

Savanna fires and their impact on net ecosystem productivity in North Australia - JASON BERINGER; LINDSAY B. HUTLEY; NIGEL J. TAPPER; LUCAS A. CERNUSAK (Global Change Biology, 2007)

Evolution of maritime continent thunderstorms under varying meteorological conditions over the Tiwi Islands - Jason Beringer; Nigel J. Tapper; Tom D. Keenan (International Journal of Climatology, 2001)
The development of tropical island thunderstorms in the maritime continent were investigated over the Tiwi Islands to the north of the Australian continent. A satellite cloud climatology was developed to examine these island thunderstorms, locally known as Hectors. During the pre‐monsoon period of 1990 and 1991 Hectors were observed on 70% of days. These Hectors were observed to occur under two distinct environmental flow regimes. Under easterly flow, development occurred on the western end of the island and conversely under westerly flow, development occurred to the east. Hectors were also observed to have three distinct modes of development (Hector, suppressed and late developing) and one mode of non‐development (non‐Hector). Satellite cloud climatologies were developed and mean atmospheric characteristics were determined for each of these development modes. Hectors developed under conditions of moderate convective available potential energy, moderate shear and high moisture availability. Sub‐cloud layer winds were also thought to contribute to the structure of the storm. Non‐Hector and suppressed Hector days usually occurred after a previous convective disturbance such as a monsoon low or squall line and had typically low convective available potential energy and high values of convective inhibition. Conditions for late developing Hectors appeared to be conducive for thunderstorm development with high convective available potential energy and low values of convective inhibition. However, early initiation was suppressed by high shear conditions. Development in the late developing mode could be more intense than in other modes. Copyright © 2001 Royal Meteorological Society

The Sensitivity of Australian Fire Danger to Climate Change - Allyson A. J. Williams; David J. Karoly; Nigel Tapper (Climatic Change, 2001)